Abused rebels and winning coalitions: Regime change under the pressure of rebellions - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2015)
We hypothesize that, in certain regime types, winning coalitions have an incentive for helping a deprived population solving the collective action problem that may otherwise restrain them in revolting against an incumbent. Recent selectorate literature holds that members of a winning coalition may find themselves in a loyalty trap after having realized a bad character of an incumbent. According to our hypothesis, the winning coalition's members can find a way out of the loyalty trap by influencing expectations within the population in a way as to spark a public rebellion. A thus induced rebellion raises the chance of each of the winning coalition's members for preserving their position in a newly formed winning coalition following a regime change. Hence, the very regime structure that makes a loyalty trap more probably is identical to a regime structure under which we should expect a higher vulnerability to public rebellions.
Keywords: D02; D74; H11; 330